Assembly of ultrasmall Cu3N nanoparticles into three-dimensional porous monolithic aerogels. Issue 29 (12th May 2016) - Deshmukh, Rupali; Tervoort, Elena; Käch, Julian; Rechberger, Felix; Niederberger, Markus
Abstract : We present the assembly of ultrasmall Cu3 N nanoparticles into aerogels with a high surface area and porosity by thermally destabilizing colloidal nanoparticles. Abstract : We present for the first time the synthesis of transition metal nitride aerogels, specifically Cu3 N aerogels by destabilizing colloidal Cu3 N nanoparticles into gels using controlled heat treatment. The resulting aerogels consist of interconnected three-dimensional networks with ultrasmall-sized nanoparticle bridges of a surface area of 381 m 2 g −1 and only 5% relative density.